2015
DOI: 10.17843/rpmesp.2015.321.1576
|View full text |Cite
|
Sign up to set email alerts
|

Información sobre la medicación y adherencia al tratamiento antirretroviral de gran actividad en pacientes con VIH/SIDA de un hospital de Lima, Perú

Abstract: RESUMENObjetivos. Determinar la asociación entre la información sobre la medicación y adherencia al tratamiento antirretroviral de gran actividad (TARGA) en pacientes con VIH/SIDA de un hospital de Lima, Perú. Materiales y métodos. Estudio de corte transversal analítico. Por medio de entrevistas se aplicó el cuestionario SIMS (Satisfaction with Information about Medicines Scale) para medir la satisfacción con la información recibida sobre los medicamentos y el cuestionario SMAQ (Simplified Medication Adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
8
0
7
Order By: Relevance
“…Furthermore, studies [67] with small samples from the region report adherence rates for PLHIV as high as 90%. Yet, older but slightly large studies in Peru [36] identified higher adherence rates only among people with higher education (OR = 0.45. 95% CI 0.27–0.75) and age (OR = 1.05.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies [67] with small samples from the region report adherence rates for PLHIV as high as 90%. Yet, older but slightly large studies in Peru [36] identified higher adherence rates only among people with higher education (OR = 0.45. 95% CI 0.27–0.75) and age (OR = 1.05.…”
Section: Discussionmentioning
confidence: 99%
“…El paciente constantemente evalúa al médico en su (11) atención, tiempo, preocupación y explicación; además de querer recibir una información clara y (12) concreta , lo que convierte a la satisfacción del paciente en una prioridad durante el acto médico, de aquí la importancia de esta investigación, que ayudará a corregir o conservar las características de la práctica médica en 4 ciudades de nuestro país.…”
Section: Discussionunclassified
“…Por esto y otras conductas se pueden dar las críticas al proceso de atención, siendo sobre todo por el hecho de inadecuada atención, tiempo, preocupación y (9) explicación ; además de la obtención de información (10) poco clara y concreta . En el Perú se realizó un reporte que menciona que un poco menos de la mitad (11) de las atenciones no tuvieron una alta satisfacción , siendo esto evaluado sobre todo en países desarrollados, con resultados distintos obtenidos en (12)…”
Section: Introductionunclassified
“…In Lima, Peru, although the level of HIV related knowledge among PLWH has not been quantified in this context, some studies shed a light on health information and outcomes among PLWH. In a study in Lima, 77% of PLWH said that they understood all information given by the doctors [ 15 ] and a qualitative study in Piura, Peru concluded that PLWH on ARV have important misconceptions on HIV transmission and treatment and maintain sexual behaviors that can facilitate HIV transmission [ 16 ] .…”
Section: Introductionmentioning
confidence: 99%